1996
DOI: 10.1097/00000542-199610000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Small, Oral Dose of Clonidine Reduces the Incidence of Intraoperative Myocardial Ischemia in Patients Having Vascular Surgery

Abstract: A small oral dose of clonidine, given prophylactically, can reduce the incidence of perioperative myocardial ischemic episodes without affecting hemodynamic stability in patients with suspected or documented coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
9

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(51 citation statements)
references
References 19 publications
0
42
0
9
Order By: Relevance
“…General The relationship between measures of resting LV systolic function (most commonly LVEF) and perioperative events has been evaluated in several studies of subjects before noncardiac surgery. 56,58,[146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161] These studies demonstrate an association between reduced LV systolic function and perioperative complications, particularly postoperative HF. The association is strongest in patients at high risk for death.…”
Section: Supplemental Preoperative Evaluationmentioning
confidence: 57%
“…General The relationship between measures of resting LV systolic function (most commonly LVEF) and perioperative events has been evaluated in several studies of subjects before noncardiac surgery. 56,58,[146][147][148][149][150][151][152][153][154][155][156][157][158][159][160][161] These studies demonstrate an association between reduced LV systolic function and perioperative complications, particularly postoperative HF. The association is strongest in patients at high risk for death.…”
Section: Supplemental Preoperative Evaluationmentioning
confidence: 57%
“…The first randomized trials using clonidine to prevent cardiovascular complications after noncardiac surgeries demonstrated a reduction in myocardial ischemia, but no reduction in clinical events or mortality 187,188 . On the other hand, a meta-analysis has demonstrated that alpha2-agonists reduced mortality and acute myocardial infarction in patients undergoing vascular surgeries, but not in those undergoing nonvascular surgeries 189 .…”
Section: Alpha-agonistsmentioning
confidence: 99%
“…Recent reports have described the prevention of PMI/I using ABDs 6-10 and other therapeutic modalities. [11][12][13][14] Although 76% of PMI/I patients had documented risk factors, only 29% had received ABDs.…”
Section: Identification Of the Problemmentioning
confidence: 99%